2001
DOI: 10.1302/0301-620x.83b6.11995
|View full text |Cite
|
Sign up to set email alerts
|

Anterior spinal decompression in HIV-positive patients with tuberculosis

Abstract: total of 39 HIV-infected adults with spinal tuberculosis underwent anterior spinal decompression for neurological deficit. Fresh-frozen allografts were used in 38 patients. Antituberculous drugs were prescribed for 18 months, but antiretroviral therapy was not used. Six patients died within two years of surgery. Neurological recovery and allograft incorporation were observed at follow-up at a mean of 38 months, although the CD4/CD8 ratios were reversed in all patients. Adequate preoperative nutritional support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In this study, we did not explore the contribution of the CSF-derived variants to the viral population within these granulomas. In our study and previous clinical case reports it was shown that Mtb infection of the spine is extradural both in HIV-infected and HIV-uninfected patients 43 and penetration of the meninges into the spinal cord is rare, 44 thus maintaining the integrity of the blood-brain barrier. The possibility of viral trafficking between the granuloma and the CSF site cannot be ruled out, and this aspect needs to be explored in future investigations.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we did not explore the contribution of the CSF-derived variants to the viral population within these granulomas. In our study and previous clinical case reports it was shown that Mtb infection of the spine is extradural both in HIV-infected and HIV-uninfected patients 43 and penetration of the meninges into the spinal cord is rare, 44 thus maintaining the integrity of the blood-brain barrier. The possibility of viral trafficking between the granuloma and the CSF site cannot be ruled out, and this aspect needs to be explored in future investigations.…”
Section: Discussionsupporting
confidence: 66%
“…Govender et al [20] 's average ESR value in their 39 HIV positive patients was 91 mm/h. While Guo et al [21] shows an average ESR of 79.4 mm/h of their 67 TB spondylitis patients.…”
Section: Discussionmentioning
confidence: 84%
“…TH1 is essential for the attack against intracellular mycobacterium tuberculosis while TH2 has been associated with a poor clinical outcome [20] Cytokine CCL7 is released by platelets causing an increase in TH-2 activity as illustrated by Feng et al [22]. Platelet count may therefore have prognostic value in the long term and further research needs to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al reported an inpatient mortality rate of 17% (Weinstein et al 2005). A cohort of 39 HIV infected patients with spinal tuberculosis showed a 15% mortality rate within two years of surgery (Govender et al, 2001). The problem of postoperative complications in HIV positive patients has been widely discussed.…”
Section: Outcomementioning
confidence: 99%
“…Similarly, Govender et al did not identify a higher incidence of wound healing disturbance in their population than that found in HIV-negative subjects. However, the ultimate outcome of surgery for HIV-infected patients depends on a number of factors, including the nature of the procedure (emergent or elective), coexisting medical problems, nutritional status, and the stage of the disease (Govender et al, 2001). …”
Section: Outcomementioning
confidence: 99%